The disease stage-associated imbalance of Th1/Th2 and Th17/Treg in uterine cervical cancer patients and their recovery with the reduction of tumor burden - Wei Lin; Hua-ling Zhang; Zhao-yuan Niu; Zhen Wang; Yan Kong; Xing-sheng Yang; Fang Yuan (BMC, 2020)
Abstract Background Nearly all uterine cervical cancer (UCC) cases result from human papillomavirus (HPV) infection. After high-risk HPV infection, most HPV infections are naturally cleared by humoral and cell-mediated immune responses. Thus, cervical lesions of only few patients progress into cervical cancer via cervical intraepithelial neoplasia (CIN) and lead to persistent oncogenic HPV infection. This suggests that immunoregulation plays an instrumental role in the carcinogenesis. However, there was a few studies on the relation between the immunologic dissonance and clinical characteristics of UCC patients. Method We examined the related immune cells (Th1, Th2, Th17, and Treg cells) by flow cytometric analysis and analyzed their relations with UCC stages, tumor size, differentiation, histology type, lymph node metastases, and vasoinvasion. Next, we quantified the Th1, Th2, Th17, and Treg cells before and after the operation both in UCC and CIN patients. Results When compared with stage I patients, decreased levels of circulating Th1 cells and elevated levels of Th2, Th17, and Treg cells were detected in stage II patients. In addition, the imbalance of Th1/Th2 and Th17/Treg cells was related to the tumor size, lymph node metastases, and vasoinvasion. We found that immunological cell levels normalized after the operations. In general, immunological cell levels in CIN patients normalized sooner than in UCC patients. Conclusions Our findings suggested that peripheral immunological cell levels reflect the patient's condition.